Constructing the ‘Healthy Self’ on Instagram: An Appraisal and Critical Discourse Analysis of Health Narratives in Social Media Captions - Natrio, Yeyep; Yensasnidar (English Department, Faculty of Humanities, Andalas University, 2025)
This study aims to explore how the identity of “Healthy Self” is formed discursively in Instagram captions that promote ideal healthy lifestyles. It investigates the evaluative language and ideological narratives in creating self-representation through social media. The qualitative approach was employed to analyze 26 captions in English tagged with #health, #diet, #healthylifestyle, or #bodygoals. The data were examined using Appraisal Theory (Martin & White) to identify evaluative meanings and Critical Discourse Analysis (Fairclough) to interpret the ideology underlying the language use. The findings indicate that the captions express various affect, judgment, and appreciation dimensions to construct an image of “a healthy life.” Users tend to impose aspects of emotional recovery, discipline, self-acceptance, and personal empowerment. This discourse indicates a shift from traditional beauty standards towards a more balanced and compassionate approach to health. Still, it contains neoliberal ideological values such as individual responsibility, productivity, and control over the body. Instagram serves as a platform for self-expression and a discursive space that reproduces and negotiates dominant ideology about health. This study confirms the importance of critical reflection on health standards established through seemingly neutral personal narratives.